The birth of nomos - Zartaloudis, Thanos (Edinburgh : Edinburgh University Press, 2021)
An interdisciplinary study of the archaic Greek word nomos and its family of words. It includes extracts from ancient sources, in both the original and English translation, to give us a new and complete understanding of nomos and its foundational place in the Western legal tradition.
Previously issued in print: 2019.
Includes bibliographical references.
Specialized.
Description based on online resource; title from home page (viewed on May 10, 2021).
Keywords: Nomos (The Greek word); Greek philology; Classical philology; Moira (The Greek word); Language; Language teaching & learning